Evaluation of Anopheline Diversity and Abundance across Outdoor Collection Schemes Utilizing CDC Light Traps in Nchelenge District, Zambia - Christine M. Jones; Ilinca I. Ciubotariu; Mary E. Gebhardt; James Sichivula Lupiya; David Mbewe; Mbanga Muleba; Jennifer C. Stevenson; Douglas E. Norris (Insects)
In the global fight against malaria, standard vector control methods such as indoor residual spraying (IRS) and insecticide-treated nets (ITNs) are intended to protect inside residential structures and sleeping spaces. However, these methods can still leave individuals vulnerable to residual transmission from vectors that they may be exposed to outdoors. Nchelenge District in northern Zambia experiences persistently high malaria transmission even with ITNs and IRS in place. However, very few studies have examined outdoor vector activity. To assess the diversity and abundance of outdoor foraging female anopheline mosquitoes, CDC light traps were used as proxy measures for mosquito host-seeking, set in three outdoor trapping schemes randomly assigned on different nights: (1) locations where people congregate at night outside of the house within the peri-domestic space, (2) animal pens or shelters, and (3) high-human-traffic areas, such as paths to latrines, where traps were baited with BG-Lure®. A total of 1087 total female anophelines were collected over a total of 74 trap nights. Anopheles funestus s.s. comprised the majority of the collection (86%), with An. gambiae s.s. (2%) and a highly diverse sampling of other anophelines (12%) making up the remainder. Plasmodium falciparum parasites were only detected in An. funestus (1%). No significant difference in species diversity or female anopheline abundance was detected between trapping schemes. Outdoor foraging anopheline mosquitoes, including a number of infectious An. funestus, may partially explain the difficulty of controlling malaria transmission in Nchelenge District, where vector control is only targeted indoors. BG-Lure® shows some promise as an alternative to human-baited landing catch collections in this resource-poor setting.